DETERMINATION OF VOLATILE AROMA COMPOUNDS OF GANODERMA LUCIDUM BY GAS CHROMATOGRAPHY MASS SPECTROMETRY (HS-GC/MS) - Taşkın, Hatıra; Kafkas, Ebru; Çakıroğlu, Özgün; Büyükalaca, Saadet (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study was conducted at Horticulture Department of Cukurova University, Adana, Turkey during 2010-2011. Fresh sample of Ganoderma lucidum collected from Mersin province of Turkey was used as material. Volatile aroma compounds were performed by Headspace Gas Chromatography (HS-GC/MS). Alcohols, aldehydes, acids, phenol, L-Alanine, d-Alanine, 3-Methyl, 2-Butanamine, 2-Propanamine were determined. 1-Octen-3-ol (Alcohol) and 3-methyl butanal (Aldehyde) were identified as major aroma compounds.